Asthma in swimmers: A review of the current literature - Fisk, M. Z.; Steigerwald, M. D.; Smoliga, J. M.; Rundell, K. W. (The Physician and Sportsmedicine, 2010)
Asthma is common in many types of athletes, but its prevalence appears to be particularly high in swimmers. Long-term and acute exposure to swimming pool disinfectants has been shown to increase asthma risk in swimmers through inducing oxidative stress, which results in inflammation of the pulmonary epithelium and subsequent airway remodeling. Individuals with specific genotypes are more likely to develop asthma when exposed to inhaled irritants. Therefore, it is important for physicians to be knowledgeable about the risks associated with asthma in swimmers, as well as the diagnostic techniques and practices to reduce asthma symptoms.